Firearms of the Texas Rangers : From the Frontier Era to the Modern Age - Dukes, Doug (Book collections on Project MUSE., 2020)
"Book is a history of all the firearms used by the Texas Rangers, beginning with their informal establishment in 1823 and ending in the present day. Book will illustrate all the firearms, both handguns and long guns and everything in between"--